COMPENSATION AND JOB SATISFACTION FOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) EMPLOYEES OF BANK DKI - Nafiudin Nafiudin; Andari Andari; Rian Fauzi (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aimed to determine the effect of compensation and job satisfaction on Organizational Citizenship Behavior at PT Bank DKI Jakarta KCP Jatibaru. This research is motivated by increasingly fierce competition in the business world, which requires organizations to develop their human resources to support the achievement of organizational goals and maintain excellence with their competitors. The independent variable in this study is Compensation and Job Satisfaction, while the dependent variable is Organizational Citizenship Behavior. This research uses the associative descriptive method. The sampling technique used is a saturated sample, with a total sample of 30 respondents—the analytical tool used in SPSS v.24 for Windows. The results of the study prove that there is an influence between compensation and job satisfaction on Organizational Citizenship Behavior (Y) at PT Bank DKI Jakarta KCP Jatibaru with the decision Farithmetic > Ftable ( 103.524 < 3.35). The result of the coefficient of determination obtained is 0.885. This result means that compensation and job satisfaction variables affect 88.5% of Organizational Citizenship Behavior while other factors outside the research variables influence the remaining 11.5%.